Distinct representations of basic taste qualities in human gustatory cortex - Junichi Chikazoe (Nature Portfolio, 2019)
Previous research shows how taste types are represented across regions of the brain in non-human animals. Here, the authors examine how four basic tastes are represented in the human brain, showing evidence of the human gustatory cortex in the insula.